Impact of type of agricultural ODA on poverty reduction - WON, Jiyeon (KDI School, 2018)
The purpose of this study is to identify and analyze the relationships between agricultural ODA and poverty reduction in developing countries. In this paper, empirical study is conducted to identify the impact of agricultural ODA by types. According to the regression result estimated by the fixed effect model, agricultural development ODA is negatively significant. In short, if a particular agricultural ODA increases, the child mortality rate decreases, which is the proxy indicator of poverty rate in this paper.
Thesis(Master) --KDI School:Master of Development Policy,2018